2012
DOI: 10.1002/elps.201100349
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cell migration in vitro by the method based on cell patterning within microfluidic channels

Abstract: Cell migration is an early-stage and critical step for cancer metastasis. The most common approach to monitor this process is wound-healing assay. However, this traditional method has some unavoidable limitations. We observed that simply scratching the monolayer of cultured cells might cause local cell damage around the injury line. The cells along the scratched border seemed to be irritated and exhibited abnormal distribution of cytoskeleton reassembly with protruding "cell islands" and "pseudopodia" during w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Using defined patterns, cells from tumor regions could later be harvested for the gene expression analysis. Such microfluidic systems were also used to quantify cell migration as affected by chemotherapy drugs or other treatments (Wang et al, 2012). Moving to 3D culture, microfabrication using stereolithography could encapsulate MDA-MB-231, MCF-7, and MCF-10A in gelatin methacrylate to serve as a tumor model (Peela et al, 2016).…”
Section: Substrate Surface Patternsmentioning
confidence: 99%
“…Using defined patterns, cells from tumor regions could later be harvested for the gene expression analysis. Such microfluidic systems were also used to quantify cell migration as affected by chemotherapy drugs or other treatments (Wang et al, 2012). Moving to 3D culture, microfabrication using stereolithography could encapsulate MDA-MB-231, MCF-7, and MCF-10A in gelatin methacrylate to serve as a tumor model (Peela et al, 2016).…”
Section: Substrate Surface Patternsmentioning
confidence: 99%
“…Wang et al demonstrated a microfluidic wound healing assay, where cells are aligned using channels, reducing the sampling volume and processing time compared to traditional wound healing assays. 13 Tong et al on the other hand, assembled a microfluidic migration chamber at a single cell resolution for direct visualisation of chemotaxis. 14 Tay's and Whitesides' groups studied cell migration and other cell behaviour using microfluidic gradient generators and micropatterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pathak and Kumar 7 investigated the decoupled influence of the stiffness and the geometrical size of the confinement area on tumor cell migration speed by studying the morphology and migration of U373-MG human glioma cells in a polyacrylamide microchannel, which was fabricated with the aid of a PDMS mold. Wang et al 11 demonstrated a simple microfluidic device based on PDMS to form cell arrays for investigating the wound healing process. Wong et al [12][13][14] developed a new method to regulate cell growth by covering a PDMS mold with micropatterns on a polystyrene Petri dish in order to make the uncovered areas hydrophilic, while the covered parts remained hydrophobic, after treatment by oxygen plasma.…”
Section: Introductionmentioning
confidence: 99%